Approaches to Morning Glory Supply Chain Management of Tung Yee Peng Community, Ko Lanta District, Krabi Province - Chanklap, Boontaree (International Journal of Multidisciplinary in Management and Tourism, 2021)
The study is aimed to study the Morning Glory Supply Chain Model and to investigate the proper Morning Glory Supply Chain Model for Tung Yee Peng Community, Ko Lanta District, Krabi Province. The study was conducted using the area survey and discussion with a community head and Tung Yee Peng farmers and subsequently to study and design Tung Yee Peng Morning Glory Supply Chain using Soft System Methodology (SSM) (Checkland, P. (2000). Results revealed that the Morning Glory Supply Chain Model was indeed functional. The model of Tung Yee Peng Morning Glory Supply Chain was started with the Upstream Level, Tung Yee Peng farmers cultivating and harvesting their morning glory and delivering them to the distributor agent or a community head, followed by the Mid-stream Level placing emphasis on the distribution management. The distribution agent or a community head was in charge of an intermediary connecting the farmers and the morning glory buyers such as hotels, restaurants and markets in Ko Lanta. The last one was the Downstream Level consisting of ultimate consumers such as household consumers, tourists, and etc. However, the proper Morning Glory Supply Chain Model for Tung Yee Peng Community, Ko Lanta District, Krabi Province, revealed that Tung Yee Peng Morning Glory Project should focus on the supply chain management in order to get more morning glory distribution channels, including managing the amount of cultivating morning glory, which was to set the cultivating and harvesting duration. Tung Yee Peng farmers cooperated with the distribution agent and a community head and to determine the sales price, the production volume, the collection and the transfer of morning glory from Tung Yee Peng to be distributed in Ko Lanta.